Avaliação da fermentação aeróbia para produção de etanol a partir da xilose por linhagem de leveduras isoladas da casca de uva (Vitis spp) - Moraes, Debora Cristina [UNESP] (2013)
Isolate microorganisms that fermenting xylose to ethanol is a challenge to expand production of biofuels from lignocellulosic materials. For this work was tested fermentation of xylose by yeast strains isolated from grape skins (Vitis spp) in order to ethanol produce. The yeasts were grown in submerged fermentation with xylose as a carbohydrate source. Aliquots were taken every 24 hours to measure cell growth, sugar consumption and ethanol production. The yeast had an production ethanol average of 2.5 g / L and yield (Ye / s) 0.12 g / g, showing that they have the ability to produce ethanol from xylose.